Key ecological research questions for Central European forests - Ammer, Christian; Fichtner, Andreas; Fischer, Anton; Gossner, Martin M.; Meyer, Peter; Seidl, Rupert; Thomas, Frank M.; Annighöfer, Peter; Kreyling, Jürgen; Ohse, Bettina; Berger, Uta; Feldmann, Eike; et al. (Basic and applied ecology, 2018)
Forests are under pressure from accelerating global change. To cope with the multiple challenges related to global change but also to further improve forest management we need a better understanding of (1) the linkages between drivers of ecosystem change and the state and management of forest ecosystems as well as their capacity to adapt to ongoing global environmental changes, and (2) the interrelationships within and between the components of forest ecosystems. To address the resulting challenges for the state of forest ecosystems in Central Europe, we suggest 45 questions for future ecological research. We define forest ecology as studies on the abiotic and biotic components of forest ecosystems and their interactions on varying spatial and temporal scales. Our questions cover five thematic fields and correspond to the criteria selected for describing the state of Europe’s forests by policy makers, i.e. biogeochemical cycling, mortality and disturbances, productivity, biodiversity and biotic interactions, and regulation and protection. We conclude that an improved mechanistic understanding of forest ecosystems is essential for the further development of ecosystem-oriented multifunctional forest management in the face of accelerating global change.